Candida, food discipline and the dietary taming of uncertainty - Overend, Alissa (My University, 2012)
Discourses of nutritional health are strongly associated with illness, and have recently been linked to the prevalence and management of chronic undefined disorders. Using the case of Candida—a yeast-related disorder of vague symptomatology—I explore the role of food in the narratives of twenty-four people living with Candida. As Candida remains a speculative illness within the boundaries of biomedical science, it is relevant to critically explore the often-focal role of food in the management of this condition, and to consider the range of personal, social and cultural motivations at work in its dietary regulation. Taking up Foucault's theory of docility, I trace the ways in which dietary practices can be understood as normalizing the Candidad-body by helping to create a sense of certainty and control in the persistent face of illness ambiguity. In drawing on Foucault's later work, I move beyond illness dieting as solely a disciplinary regime and explore the ways in which dietary regime can also be conceptualized as a practice in the care of the self, fostering a heightened, often-changing sense of self. While Candida dieting practices will never fully operate separate from the pervasive discourses of nutritional science, they can offer productive possibilities in the regulation and maintenance of an illness not fully recognized by biomedical science.
Keywords: care of the self; Candida; undefined illness; illness dieting; food discipline